2017
DOI: 10.1016/j.mad.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Senescent intervertebral disc cells exhibit perturbed matrix homeostasis phenotype

Abstract: Aging greatly increases the risk for intervertebral disc degeneration (IDD) as a result of proteoglycan loss due to reduced synthesis and enhanced degradation of the disc matrix proteoglycan (PG). How disc matrix PG homeostasis becomes perturbed with age is not known. The goal of this study is to determine whether cellular senescence is a source of this perturbation. We demonstrated that disc cellular senescence is dramatically increased in the DNA repair-deficient Ercc1−/Δ mouse model of human progeria. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…In contrast, matrix PG synthesis capacity, assessed by 35 S‐sulphate incorporation using disc organotypic culture, was lower in discs from older, compared to younger, mice (Figure c). These in vivo correlations between disc cellular senescence and perturbed matrix homeostasis are consistent with our recent cell culture study demonstrating a matrix imbalance phenotype of senescent disc cells (Ngo, Patil et al, ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, matrix PG synthesis capacity, assessed by 35 S‐sulphate incorporation using disc organotypic culture, was lower in discs from older, compared to younger, mice (Figure c). These in vivo correlations between disc cellular senescence and perturbed matrix homeostasis are consistent with our recent cell culture study demonstrating a matrix imbalance phenotype of senescent disc cells (Ngo, Patil et al, ).…”
Section: Resultssupporting
confidence: 91%
“…Indeed, in this study, we saw a concomitant reduction in levels of the major disc protease, MMP13, and aggrecan fragmentation in Old‐GCV compared to Old‐Veh mice, suggesting cellular senescence phenotype as the source of the inflammatory proteins that trigger the degeneration cascade. This claim is substantiated by the report published by Ngo et al, which showed decreased PG synthesis capacity, enhanced aggrecan fragmentation, as well as increased production of several cytokines and matrix proteases in oxidative stress‐induced senescent human NP cells (Ngo, Patil et al, ). Together, these studies support the causal role for senescent cells in driving matrix homeostatic imbalance in aging discs.…”
Section: Discussionmentioning
confidence: 66%
“…These H 2 O 2 ‐induced senescent disc cells exhibited SASP, as characterized by their secretion of high levels of MMPs and pro‐inflammatory cytokines. These senescent disc cells also showed growth arrest and perturbed matrix homeostasis, that is, reduced matrix synthesis capacity (anabolism) and increased matrix degradation (catabolism) . However, to determine the causative role of cellular senescence in driving disc aging, genetic and pharmacological in vivo strategies are needed to study the effects of ablation of senescent cells on age‐associated IDD.…”
Section: Biochemical Cascade Of Intervertebral Disc Agingmentioning
confidence: 99%
“…One of the major features of IDD is decrease of the proteoglycan (PG) content of IVDs (23). LPS, an admitted strong promoter of inflammation, can reduce the PG content, thus leading to IDD (24,25).…”
Section: Discussionmentioning
confidence: 99%